SOCIAL VALUES IN ANANTA TOER’S NOVEL “BUMI MANUSIA” - Feni Aisyah; M. Manugeren; Purwarno Purwarno (AICLL: ANNUAL INTERNATIONAL CONFERENCE ON LANGUAGE AND LITERATURE, 2020)
This research focused on the types of social values reflected in Ananta Toer’s novel entitled Bumi Manusia. This novel successfully describes not only the cultural revolution in a colonized country but also an objection against the absolute supremacy of cultural and social values. The research was aimed at revealing the kinds of social values in the novel. The data were in the forms of sentences, paragraphs and dialogues referring to social values such as positive and negative social values. The method used in this research is descriptive qualitative method with content analysis technique, that is by analyzing the letters, words, sentences and verses that can explain some social values in this novel. Based on the research finding and discussion, as well as the theory of social values proposed by Notonegoro (2014), the social values are divided into Value of truth, Aesthetic value, Moral value and Religious value. The results show that there are four types of social value in the novel: Value of truth (Justice), Aesthetic value (love), Moral value (encouraging kinship and politeness) and Religious value (patience and faith).